Mayumi the forest pig - Shaw, Rachel, L. (The Bookmark, Inc., 2015)
"Mayumi the forest pig. Mayumi is a Visayan Warty Pig. She is a curious young pig and likes to play and explore the forest that is her home. She doesn't mind when she gets separated from her family until nightfall when the noises of the forest are scary and she realizes she does need her family after all. Pigs like Mayumi live on the islands of Negros and Panay in the Philippines. All the animals she meets are found on the same islands. Most of them are found nowhere else."